DESAIN PROGRAM TAHFIDZ AL-QUR’AN DI SEKOLAH MENENGAH PERTAMA (SMP) ISLAM AL-AZHAR 48 SAMARINDA - Muchammad Rifai Hamzah (Berkah Smart Academica, 2024)
Design is a series of planning and implementation. Something interesting would be if the formal curriculum were designed by collaborating with the non-formal curriculum, namely the mandatory tahfidz program for students at Al-Azhar 48 Samarinda Islamic Middle School. Therefore, the aim of this research is to examine the design of the tahfidz Al-Qur'an program at Islamic Middle School 48 Al-Azhar Samarinda. This research method uses descriptive qualitative with a field research approach. Collection techniques by means of observation, interviews and documentation. Then analyze the data by condensing data, displaying and concluding. For data validity, data triangulation techniques are used, namely data cross-check synchronization. So it can be concluded from the results of this research that the design used is a) The planning stage, namely determining responsibilities, determining goals, determining time allocation and schedule. b) Implementation stage, namely carrying out what has been planned. c) Evaluation stage, namely evaluation through religious monitoring books, rolling evaluations, semester evaluations. With this design, Al-Azhar 48 Samarinda Islamic Middle School succeeded in producing a Qur'any generation. At least these results can be seen once a year at every tahfidz graduation.